Processing–Structure–Properties of Cork Polymer Composites - Martins, Carla I.; Gil, Vitória (Frontiers in Materials, 2020)
This work aims at presenting a new strategy for the use of cork by-products on the development of sustainable composites with potential applications in rotational molding. In this study different cork granulometries (0.15 to 3 mm) and matrix/cork ratios (90/10, 85/15, 80/20) are analyzed to access the processability of medium density polyethylene (PE) with cork by rotational molding. The influence of processing parameters, such as the mold peak internal air temperature (200-240ºC) is analyzed and correlated to the aesthetics, morphological and mechanical properties of the parts. The aim is to obtain a complete understanding of the processing-structure-properties relationships. Defect free parts are obtained with thin granulometric cork powders at maximum of 10% by weight in PE/cork composites. The increase of cork content reduces the sintering capability, increases porosity, wall thickness and surface defects and, simultaneously, weakening the mechanical properties. The increase of peak internal air temperature (PIAT) inside the mold favors a more compact structure and reveals better impact properties. All the parts are soft on touch and transmit the comfort and sensation of warm feeling of the cork. Moreover, lightweight parts and hydrophobic surface is achieved from the cork intrinsic properties. As a natural material, cork darkens its color with temperature which is attributed to the reactions of the extractives within the components of cork, with no degradation associated. The work shows that polymer cork composites (CPC) are suitable for rotational molding within the processing window characteristic of PE, to achieve innovative and sustainable products with unique aesthetics and functionalities given by cork material.